2017
DOI: 10.3389/fpsyg.2017.00487
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Indian Caste Identity and Caste Inconsistent Norms on Status Representation

Abstract: The Indian caste system is a complex social structure wherein social roles like one’s profession became ‘hereditary,’ resulting in restricted social mobility and fixed status hierarchies. Furthermore, we argue that the inherent property of caste heightens group identification with one’s caste. Highly identified group members would protect the identity of the group in situations when group norms are violated. In this paper, we were interested in examining the consequence of caste norm violation and how an indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 50 publications
0
49
1
Order By: Relevance
“…All subcastes in a region are ranked. Marriage of a woman from a higher-ranked subcaste to a man of a lower-ranked subcaste impairs the honor of the higher-ranked subcaste; in North India, the offense is frequently avenged by honor killings of the bride and groom (34). In their open-ended responses to this vignette, 57% of high-caste respondents mentioned izzat, roughly translated as "male honor," compared with only 27% of low-caste respondents.…”
Section: Resultsmentioning
confidence: 90%
“…All subcastes in a region are ranked. Marriage of a woman from a higher-ranked subcaste to a man of a lower-ranked subcaste impairs the honor of the higher-ranked subcaste; in North India, the offense is frequently avenged by honor killings of the bride and groom (34). In their open-ended responses to this vignette, 57% of high-caste respondents mentioned izzat, roughly translated as "male honor," compared with only 27% of low-caste respondents.…”
Section: Resultsmentioning
confidence: 90%
“…In line with our predictions, we found that an observer experiences greater threat when faced with an ingroup rather than an outgroup offender, and in turn assigns more utilitarian punishment to this offender. This finding is in line with prior research which suggests that people experience increased identity threat when deviant members come from the ingroup rather than the outgroup (Okimoto & Wenzel, ; Rullo et al ., ; Sankaran et al ., ; Van der Toorn et al ., ). To the best of our knowledge, this research is the first to show that people display stronger preference for (specifically) exclusionary punishments against ingroup offenders through the experience of increased ingroup threat.…”
Section: Discussionmentioning
confidence: 97%
“…Further, we hypothesize that perceived ingroup identity threat should mediate the effect of offender's group membership and ingroup typicality on justice decisions. People experience increased identity threat when deviant members come from the ingroup rather than the outgroup (Okimoto & Wenzel, 2010;Rullo et al, 2015;Sankaran et al, 2017;Van der Toorn et al, 2015) and when they are typical rather than atypical ingroup members (Levine & Moreland, 2002;Meeussen et al, 2012). This is because group values and reputation are highly jeopardized in such cases.…”
Section: Aims Of the Study And Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Forward castes /communities (FCs) comprise those of the more privileged high caste individuals. The FCs have historically been and, continuous to be, in a strong socioeconomic position with the highest status in society (Sankaran et al, 2017).…”
Section: Introductionmentioning
confidence: 99%